Ruimtelike en temporele leksikografiese deiktiese verankering - Gouws, Rufus H. (Lexikos, 2022)
Spatial and Temporal Lexicographic Deictic Anchoring. In this contribution attention is given to deixis as it is known in the field of semantics. The transfer of deixis to lexicography is discussed and the concept of lexicographic deictic anchoring is brought to the fore. It is shown how this anchoring can be executed in different ways. Lexicographers need to decide how to employ this procedure in a specific dictionary. Different types of text segments can be used to enable deictic anchoring. These segments that include items, item symbols and item parts are briefly discussed.The main focus of this article is on spatial and temporal lexicographic deictic anchoring. Different deictic markers and anchoring procedures are discussed. In this regard it is shown that dictionaries do not only employ single items but also item complexes and that these item complexes can have a uniform or a hybrid format. It is suggested that successful deictic anchoring often demands that dictionaries should complement a primary anchoring procedure with secondary anchoring procedures. Deictic anchoring is discussed as a multi-phased process. The discussion is illustrated by real examples from dictionaries. Following the discussion suggestions are made for improved procedures of lexicographic deictic anchoring.Keywords: deictic anchoring, hybrid item complex, internally-expanded item, item symbol, lexicographic deictic centre, lexicographic deixis, lexicographic labels, neologisms, primary deictic item, rudimentary deictic anchoring, secondary deictic item